Race‐Specific Pharmacodynamic Model of Propofol‐Induced Loss of Consciousness. (28th March 2016) - Lampotang, Samsun; Lizdas, David E.; Derendorf, Hartmut; Gravenstein, Nikolaus; Lok, Benjamin; Quarles, John P.
Abstract: We present a race‐specific model of propofol‐induced loss of consciousness that is based on pharmacodynamic data collected and adapted from the peer‐reviewed literature. In the proposed race‐specific model that includes EC05 and EC95 concentrations, the median (EC50) (and where available 95%CI) propofol concentrations at the effect site compartment for propofol‐induced loss of consciousness for whites, Chinese, blacks, and Indians are 2.8 (2.7‐2.9), 2.2 (2.2‐2.3), 2.0, and 1.9 μg/mL, respectively.